PENGARUH VOLUNTARY DISCLOSURE PADA EARNINGS RESPONSE COEFFICIENT - Sudarma, I Putu; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2015)
Earnings quality is important for those who use financial statements for purposes of the contract and making investment decisions . One measure of the quality of earnings is Earnings Response Coefficient ( ERC ) . The purpose of this study was to determine the effect of Voluntaray Disclosure on Earnings Response Coefficient . This research was conducted on companies listed in Indonesia Stock Exchange 2009-2013 period . Samples was determined using the method of probability sampling is stratified random sampling . The number of samples selected were 347 companies observations . Data analysis method used is a simple linear regression analysis . Based on the analysis that has been done , this study proves that voluntary disclosure negative effect on the ERC . On average a relatively small voluntary disclosure causes voluntary disclosure by the company less response or give a negative signal to the users of financial statements .
Keywords: Voluntary Disclosure, Cummulative Abnormal Return, Unexpected Earnings, Earnings Response Coefficient